ANALISIS PERANAN PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA BANJARMASIN - HARIS NOVITRI SUBHANNOR (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2018)
The research method used is quantitative descriptive analysis by using secondary and primary data, through the collection of information and data available at the Regional Financial Agency of Banjarmasin City and related agencies, as well as the literature that is related to this research and conduct interviews or direct interviews with relevant agencies.Based on the above calculation, the efforts that must be done by the Regional Government, especially the Regional Finance Agency of Banjarmasin City are among others: multiplying the event about taxes that appeal to the public, increasing the socialization of the importance of paying taxes, providing transparency about tax income, increasing attractiveness pariwisaata in order to be able to steal visitors to the hotel as well as kerestoran, and provide easy access from the procedures of registering or paying taxes.